2014
DOI: 10.1186/1471-2458-14-1242
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining relevance: an evaluation of health message sponsorship at Australian community sport and arts events

Abstract: BackgroundHealth message sponsorship at community sport and arts events is an established component of a health promotion settings approach. Recent increases in commercial sponsorship of sport and community events has swelled competition for consumer attention and potentially reduced the impact of health message sponsorship. The purpose of this study was to evaluate awareness, understandings and behavioural intentions of health messages promoted at sponsored community sport and arts events.MethodsInterview and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Research indicates that sponsorship can increase brand awareness, modify brand image and increase intentions to purchase sponsor products [1416]. Similarly, health messages within a comprehensive sponsorship program can successfully build awareness and behavioural intention among people attending sport and arts events [17]. Exposure to elite sport sponsorship by alcohol and tobacco brands is positively associated with consumption of sponsors’ products [15, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that sponsorship can increase brand awareness, modify brand image and increase intentions to purchase sponsor products [1416]. Similarly, health messages within a comprehensive sponsorship program can successfully build awareness and behavioural intention among people attending sport and arts events [17]. Exposure to elite sport sponsorship by alcohol and tobacco brands is positively associated with consumption of sponsors’ products [15, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The first group of sponsorships primarily targeted organisations. It included eight Healthway sponsorship programme evaluation studies focused on sport, arts and racing organisations (Corti et al , 1995; Corti et al , 1997b; Donovan et al , 1997; Holman et al , 1996; Holman et al , 1997; Giles-Corti et al , 2001; Oddy et al , 1995; Rosenberg and Ferguson, 2014) and two VicHealth sponsorship programme evaluation studies (Crisp and Swerissen, 2003; Dobbinson et al , 2006). In contrast, the primary foci of VicHealth’s sponsorship were sporting and other organisations promoting healthy environments in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Policy was the main aim in two large sponsorship programmes provided by Healthway and VicHealth. Eight studies evaluating the Healthway sponsorship programme (Corti et al , 1995; Corti et al , 1997b; Donovan et al , 1997; Holman et al , 1996; Holman et al , 1997; Giles-Corti et al , 2001; Oddy et al , 1995; Rosenberg and Ferguson, 2014) and two studies evaluating different elements of the VicHealth sponsorship programme (Crisp and Swerissen, 2003; Dobbinson et al , 2006) reported policy aims. The main purpose of Healthway’s sponsorship programme was to create a healthy environment through structural changes at events, such as introduction of smoke-free policies and provisioning of healthy food choices (Holman et al , 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Offering an interactive environment, informal venues such as music festivals or mass sports events are effective settings to foster community receptiveness for behaviour change towards healthier lifestyles. [3][4][5] Sports captivate the attention of countless fans, providing entertainment and joy to both athletes and spectators, and eliciting a contagious wave of emotional connection that gathers and engages the interest and participation of large audiences. As posited by the social cognitive theory's (SCT) concept of modelling, 6 even if not actively engaged in the practice of sports, passers-by and the spectators of the event can experience a self-reflection upon their own health-oriented values and physical activity habits; in other words, sport events can trigger a behavioural change towards healthier lifestyles.…”
Section: Publicly Stressing the Role Of Mitochondria In Nafld With(inmentioning
confidence: 99%
“…4,7,8 Furthermore, the receptivity and effectiveness of health-oriented messages seem to be further increased when perceived as matching with the nature of the event and supported by a wider media campaign. 5,9,10 Thus, sports events provide the ideal setting for promoting exercise as an ally for the prevention and treatment of NAFLD and other sedentary-driven contemporary metabolic disorders.…”
Section: Publicly Stressing the Role Of Mitochondria In Nafld With(inmentioning
confidence: 99%